فکر اسلامی کے فروغ میں امام احمد رضا کا کردار اور عصر حاضر: The Role of Imam Ahmad Raza in The Promotion of Islamic Thought and Current Era - Dr. Muhammad Naveed Iqbal; Dr. Hafiz Abdul Haseeb (Al Manhal Research Journal, 2023)
Islamic thought is the name of deeply studying Islam externally and internally and presenting it to the world from different aspects not only as a religion but also as a thought and theory in life. Imam Ahmad Raza undoubtedly, was a great Mujadid, a great jurist and a great intellectual. He had a sensitive eye on the internal and external problems and difficulties of the Muslim Ummah. The focus of his thought and vision was that the Islamic thought should dominate every civilization of the world and the Muslim nation should be higher than every nation in the world. It is the wisdom of God that He blesses every great personality according to the needs and requirements of that time. In the era of Ghazali, philosophy was order of the day, so he was given full knowledge of Islamic wisdom and knowledge against crude principles of philosophy. During the reign of Mujadid Alf e Sani,there was an attack on the greatness of Tawheed, he was forced to express the indisputable truths of Tawheed. So he was equipped with intellectual and spiritual sciences. Similarly, in the 20th century, the honor of Prophet hood was attacked from four sides, by the Aryas, the British, and their fellow men, in this situation, ALLAH, whom blessed him with undeniable abilities of reasoning, and he was blessed with the teachings of the Holy Prophet, peace and blessings be upon him. He rendered great service in the promotion of Islamic thought. Ended the ways against the Shariah, and revealed the path of the Sunnah against the disbelievers.